Architectural Drawing as Depiction and Proposal - Martha Abbott (Oz, 1988)
As architects we often regard drawing as a vehicle for communication. For some drawing is a means to illustrate an idea or solve a technical problem. Throughout history, architects have used drawing to represent building...